The Role of Wardah Cosmetic Brand Image through Social Media Based Branding Strategies - Kusmarini, Kusmarini; Kurniawati, Wiza; Ulfah, Fadilla; Mayasari, Mayasari; Arief, Hidayatul (The Future of Education Journal, 2026)
The rapid growth of social media usage has transformed marketing communication strategies used by companies, including in the cosmetic industry. Social media platforms enable companies to reach consumers more widely, interact directly, and build brand identity effectively. This study aims to analyze the role of social media branding strategies in building the brand image of Wardah cosmetics. The research employs a literature review approach by examining relevant scientific journals, books, and previous studies related to digital marketing, branding strategies, social media, and brand image. Data were collected through literature searching, reading, and classifying relevant information from credible academic sources. The data were examined using a descriptive qualitative method to integrate findings from previous research.The results indicate that the use of social media platforms such as Instagram, TikTok, and YouTube plays an important role in strengthening Wardah’s brand image through creative content, consistent brand communication, and collaboration with influencers. Social media also supports the development of positive consumer perceptions and stronger brand awareness in the digital era.